Identification of novel deletion breakpoints bordered by segmental duplications in the NF1 locus using high resolution array-CGH. Issue 1 (8th June 2005) - Mantripragada, K K; Thuresson, A-C; Piotrowski, A; Díaz de Ståhl, T; Menzel, U; Grigelionis, G; Ferner, R E; Griffiths, S; Bolund, L; Mautner, V; Nordling, M; Legius, E; et al.
Abstract : Background: Segmental duplications flanking the neurofibromatosis type 1 ( NF1 ) gene locus on 17q11 mediate most gene deletions in NF1 patients. However, the large size of the gene and the complexity of the locus architecture pose difficulties in deletion analysis. We report the construction and application of the first NF1 locus specific microarray, covering 2.24 Mb of 17q11, using a non-redundant approach for array design. The average resolution of analysis for the array is ∼12 kb per measurement point with an increased average resolution of 6.4 kb for the NF1 gene. Methods: We performed a comprehensive array-CGH analysis of 161 NF1 derived samples and identified heterozygous deletions of various sizes in 39 cases. The typical deletion was identified in 26 cases, whereas 13 samples showed atypical deletion profiles. Results: The size of the atypical deletions, contained within the segment covered by the array, ranged from 6 kb to 1.6 Mb and their breakpoints could be accurately determined. Moreover, 10 atypical deletions were observed to share a common breakpoint either on the proximal or distal end of the deletion. The deletions identified by array-CGH were independently confirmed using multiplex ligation-dependent probe amplification. Bioinformatic analysis of the entire locus identified 33 segmental duplications. Conclusions: We show that at least one of these segmental duplications, which borders the proximal breakpoint located within the NF1 intron 1 in five atypical deletions, might represent a novel hot spot for deletions. Our array constitutes a novel and reliable tool offering significantly improved diagnostics for this common disorder.